THE INFLUENCE OF BRAND EXPERIENCE AND BRAND PERSONALITY ON BRAND LOYALTY THROUGH BRAND LOVE - Julia Angelina; RA Nurlinda (Sean Institute, 2023)
This research investigates the direct effect of brand experience and brand personality on brand love. It determines the immediate impact of brand experience, brand personality, and brand love on brand loyalty, as well as the indirect influence of brand experience and brand personality on brand loyalty through brand love for Avoskin skincare. This study used the path analysis method, and data collection was done using a questionnaire distributed online using google forms. The questionnaires collected are 160 respondents using the purposive sampling method as the sample collecting technique. From the results of the study, it was found that brand experience and brand personality have a positive effect on brand love. Brand experience and brand love positively affect brand loyalty, while brand personality does not affect brand loyalty. Brand experience and brand personality have a positive impact on brand loyalty through brand love. Therefore, Avoskin needs to increase brand experience and brand love because consumers who have positive experiences and high love for the brand can make repeat purchases and have a high level of loyalty to the brand.